Ko-Insiden Rhinosinusitis Kronis dengan Polip Hidung dan Neurofibroma - Dolly Irfandy; Bestari Jaka Budiman; Khairani Ayunanda Ikhlas; Pamelia Mayorita (PERHATI-KL, 2023)
Background: Nasal polyps are painless inflammatory lesions originated from around the middlemeatus or paranasal sinus cavity; while neurofibroma is benign peripheral nerve sheath tumor. Purpose:To report a rare case of neurofibroma concurrently with nasal polyps in chronic rhinosinusitis. Casereport: A 64-year-old female with chief complaint congestion on the right nose cavity. There was a mass on both nasal cavities. Patient diagnosed with benign mass at right nasal cavity and chronic rhinosinusitis with nasal polyps at left nasal cavity; with a differential diagnosis of chronic rhinosinusitis with bilateral nasal polyps. Computer tomography scan results showed homogeneous isodense lesion in the right nasal cavity, and mucosal thickening in left nasal cavity and maxillary sinus. Patient was managed with total extirpation of the bilateral nasal cavity mass and functional endoscopic sinus surgery. Pathological examination revealed neurofibroma in the right nasal cavity and polyps in the left nasal cavity. Clinical question: “How to differentiate inflammation with tumor of nasal and paranasal sinuses? Is there a causal relationship?” Review method: Literature searching was performed with the keywords “nasal cavity neurofibroma”, AND “nasal polyps”, AND ”chronic rhinosinusitis” through database Google Scholar, PubMed, and hand searching/e-book. Result: There were 11 literatures published in the last 5 years, and 7 articles relevant with the subject. Conclusion: Chronic rhinosinusitis with nasal polyps, along with neurofibroma on nasal cavity is a rare co-incidence, and there was no correlation between those lesions. Pathological examination is a gold standard in differentiating a definite diagnosis of neurofibromas and polyps.Keywords: nasal cavity neurofibroma, nasal polyps, chronic rhinosinusitis